A mediational model of obesity related disordered eating: The roles of childhood emotional abuse and self-perception. (August 2017) - Hymowitz, Genna; Salwen, Jessica; Salis, Katie Lee
Abstract: The extant literature indicates negative self-perceptions are a risk factor for disordered eating (DE) and DE is a risk factor for overweight and obesity. While childhood emotional abuse (EA) is often linked to DE and obesity, it is typically not included in comprehensive models of these health problems. Further investigation of interactions among EA, self-perception, and DE is needed to refine treatments for overweight, obesity, and DE. This study evaluated a model of DE and weight difficulties in which negative self-perception mediate the relationship between EA and DE, and DE predicts body mass index (BMI) in a population of emerging adults. Further, this study investigated the utility of history of EA for prediction of DE and classification of individuals with and without DE. Self-report questionnaires on childhood trauma, psychopathology, and eating behaviors were administered to 598 undergraduate students. Latent variable analysis confirmed the hypothesized model. Recursive partitioning determined that individuals reporting a high level of EA likely meet criteria for night eating syndrome (NES) or binge eating disorder (BED), and history of EA has a moderate to high level of specificity as a predictor of BED and NES. These findings confirm the necessity of evaluating EA and DE in emerging adults with weight difficulties, and the importance of assessing self-perception and DE in individuals with a history of EA. Future studies should investigate the utility of addressing EA and self-perception in interventions for DE and obesity and to determine whether these findings can be generalized to a clinical population. Graphical abstract: Mediational model of the relationships among childhood emotional abuse (EA), self-perception, disordered eating (DE), and obesity. For the relationship between EA and DE, 0.60 is the unmediated beta and 0.25 is the beta after inclusion of Self-perception as a mediator. *** p < 0.001. BE = Binge Eating. NES = Night Eating Syndrome. UWC = Unhealthy Weight Control Behaviors. BMI = Body Mass Index. Highlights: Emotional abuse predicts cognitive bias, disordered eating, weight difficulty. Clinical cutoffs on a measure of emotional abuse can predict disordered eating. Emotional abuse should be assessed in individuals with overweight/obesity.